הערבים בעיניין מזרחיות: יצירתו של בורלא בשנות העשרים והשלושים - אופנהיימר יוחאי (מכאן, 2008)
Yehuda Burla (1886-1969) used to present himself as a "Sephardic writer" and focused his literary writings on the Jewish Sephardic community in the land of Israel and throughout the Middle East, literary critics stressed the anthropological-social aspect of his literature and his naive, non-modernistic poetics; assuming that he uncritically represented the Zionistic Orientalist ideology concerning the Arab which was shared by most Hebrew writers of the pre-state era. This article, however, delineates three different stages in Burla’s writings about the Arab. the first Orientalist stage (till 1920); the second stage (and the most revolutionary) in which he dismissed Zionistic hegemonic perspective, trying to develop a new Mizrachi ethnical and non-national narrative, for the first time in modern Hebrew literature (till 1929); the third stage, after the increasing national conflicts of 1929 and the 3O ׳S, where he fully adopted Zionistic national perspective and adhered to it even after 1948 . This inner polarization in the writings of Burla, as well as the first shift between etlinical and national perspectives, remained unnoticed in literary criticism.